Including the sub-grid scale plume rise of vegetation fires in low resolution atmospheric transport models - Freitas, S. R.; Carvalho, J. A. [UNESP]; Longo, K. M.; Chatfield, R.; Latham, D.; Silva Dias, M. A F; Andreae, M. O.; Prins, E.; Santos, J. C.; Gielow, R. (Copernicus Publications, 2007)
We describe and begin to evaluate a parameterization to include the vertical transport of hot gases and particles emitted from biomass burning in low resolution atmospheric-chemistry transport models. This sub-grid transport mechanism is simulated by embedding a 1-D cloud-resolving model with appropriate lower boundary conditions in each column of the 3-D host model. Through assimilation of remote sensing fire products, we recognize which columns have fires. Using a land use dataset appropriate fire properties are selected. The host model provides the environmental conditions, allowing the plume rise to be simulated explicitly. The derived height of the plume is then used in the source emission field of the host model to determine the effective injection height, releasing the material emitted during the flaming phase at this height. Model results are compared with CO aircraft profiles from an Amazon basin field campaign and with satellite data, showing the huge impact that this mechanism has on model performance. We also show the relative role of each main vertical transport mechanisms, shallow and deep moist convection and the pyro-convection (dry or moist) induced by vegetation fires, on the distribution of biomass burning CO emissions in the troposphere.
Keywords: airborne survey; atmospheric chemistry; atmospheric modeling; atmospheric plume; atmospheric transport; biomass burning; carbon monoxide; model validation; one-dimensional modeling; satellite data; three-dimensional modeling; troposphere; vegetation; vertical distribution; wildfire; Amazon Basin; South America